Long-term safety and efficacy of deutetrabenazine for the treatment of tardive dyskinesia. Issue 12 (10th July 2019) - Fernandez, Hubert H; Stamler, David; Davis, Mat D; Factor, Stewart A; Hauser, Robert A; Jimenez-Shahed, Joohi; Ondo, William G; Jarskog, L Fredrik; Woods, Scott W; Bega, Danny; LeDoux, Mark S; Shprecher, David R; et al.
Abstract : Objective: To evaluate the long-term safety and efficacy of deutetrabenazine in patients with tardive dyskinesia (TD). Method: Patients with TD who completed the 12 week, phase 3, placebo-controlled trials were eligible to enter this open-label, single-arm study. The open-label study consisted of a 6 week dose-escalation phase and a long-term maintenance phase (clinic visits at Weeks 4, 6 and 15, and every 13 weeks until Week 106). Patients began deutetrabenazine at 12 mg/day, titrating up to a dose that was tolerable and provided adequate dyskinesia control, based on investigator judgement, with a maximum allowed dose of 48 mg/day (36 mg/day for patients taking strong cytochrome P450 2D6 (CYP2D6) inhibitors). Safety measures included incidence of adverse events (AEs) and scales used to monitor parkinsonism, akathisia/restlessness, anxiety, depression, suicidality and somnolence/sedation. Efficacy endpoints included the change in Abnormal Involuntary Movement Scale (AIMS) score (items 1 to 7) from baseline and the proportion of patients rated as 'Much Improved' or 'Very Much Improved' on the Clinical Global Impression of Change. Results: A total of 343 patients enrolled in the extension study, and there were 331 patient-years of exposure in this analysis. The exposure-adjusted incidence rates of AEs with long-term treatment were comparable to or lower than those observed in the phase 3 trials. The mean (SE) change in AIMS score was –4.9 (0.4) at Week 54 (n = 146), – 6.3 (0.7) at Week 80 (n = 66) and –5.1 (2.0) at Week 106 (n = 8). Conclusions: Overall, long-term treatment with deutetrabenazine was efficacious, safe, and well tolerated in patients with TD. Trial registration number: NCT02198794 .